Distribution of apple and blackcurrant microbiota in Lithuania and the Czech Republic - Vepštaitė-Monstavičė, Iglė; Lukša, Juliana; Stanevičienė, Ramunė; Strazdaitė-Žielienė, Živilė; Yurchenko, Vyacheslav; Serva, Saulius; Servienė, Elena (Microbiological research, 2018)
The microbial assemblies on the surface of plants correlate with specific climatic features, suggesting a direct link between environmental conditions and microbial inhabitation patterns. At the same time however, microbial communities demonstrate distinct profiles depending on the plant species and region of origin. In this study, we report Next Generation Sequencing-based metagenomic analysis of microbial communities associated with apple and blackcurrant fruits harvested from Lithuania and the Czech Republic. Differences in the taxonomic composition of eukaryotic and prokaryotic microorganisms were observed between plant types. Our results revealed limited geographic differentiation between the bacterial and fungal communities associated with apples. In contrast, blackcurrant berries harvested from different regions demonstrated high diversity in both bacterial and fungal microbiota structures. Among fungal and bacterial microorganisms, we identified both potentially beneficial (Cryptococcus, Hanseniaspora, Massilia, Rhodotorula, Sphingomonas) and phytopathogenic microorganisms (Cladosporium, Pantoea, Phoma, Pseudomonas, Septoria, Taphrina) indicating their important roles in ecological and evolutionary processes.
Keywords: DNA fungální; DNA, Fungal; metagenomika; DNA bakterií; Blackcurrant; Phylogeny; Fungi; Microbial Consortia; mikrobiota; houby; Microbiota; Metagenomics; Apple; Lithuania; DNA, Bacterial; Litva; fylogeneze; Metagenomic analysis; Czech Republic; ovoce; Fruit; Bacteria; ekologie; Malus; Ribes; Česká republika; mikrobiální společenstva; Ecology